An update on the distribution and nomenclature of fleas (Order Siphonaptera) of bats (Order Chiroptera) and rodents (Order Rodentia) from La Rioja Province, Argentina - Berrizbeitia, M. Fernanda López (Zookeys, 2017)
Abstract. The mammalian and flea fauna of La Rioja Province is one of the least known from northwestern Argentina. In this study, the distribution and nomenclature of 13 species of fleas of bats and rodents from La Rioja Province are updated. Four species of fleas are recorded for the first time in La Rioja Province including a new record for northwestern Argentina, and two new flea-host associations. An identification key and distribution map are included for all known species of Siphonaptera of bats and rodents from La Rioja Province, Argentina.